Desain Ulang Area Kerja Prakarya Berbasis Antropometri di Sekolah Menengah Kejuruan (SMK) - Sari, Resy Kumala; Adeswastoto, Hanantatur; Yusmita, Yesi; Hardianti, Sri; Tanjung, Lailatul Syifa (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2022)
The handicraft work area in Vocational High Schools (SMK) often fails to consider the suitability of table and chair dimensions with students' body measurements. This mismatch poses risks such as muscle fatigue, back pain, and reduced comfort and learning productivity. This community service project aims to redesign the handicraft work area based on students’ anthropometric data to create an ergonomic environment that supports healthy and productive learning. The methods include collecting students’ anthropometric data, analyzing furniture suitability, conducting ergonomic education sessions, and simulating the use of redesigned tables and chairs. The activity was conducted at SMK Muhammadiyah, Tuah Madani Subdistrict, Pekanbaru City, involving 20 students and 5 handicraft teachers. The results showed an increase in ergonomic awareness, identification of furniture mismatches, and positive acceptance of the new design, which provides greater comfort and supports handicraft learning activities.